2002
DOI: 10.1046/j.1365-2672.2002.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular characterization of chickpea rhizobia isolated from different areas of Morocco

Abstract: Aims: To determine the biodiversity of rhizobial strains nodulating Cicer arietinum L. in representative soils from various areas of Morocco. Methods and Results: Symbiotic traits, utilization of 49 carbohydrate sources, resistance to antibiotics and heavy metals, tolerance to salinity, to extreme temperatures and pH were studied as phenotypic markers. In addition, restriction fragment length polymorphism (RFLP) of PCR-amplified 16S rDNAs were compared with those of reference strains. Numerical analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
66
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 38 publications
(99 reference statements)
16
66
4
Order By: Relevance
“…The sequence of the nifH gene showed 99.6% similarity with several strains of Mesorhizobium ciceri reported to nodulate chickpea in Africa (25). These results differ from those obtained previously based on nifD sequences from Bradyrhizobium strains that showed a great degree of local divergence (36); nevertheless, additional studies including other rhizobial species from various geographical locations should be performed to establish definitive conclusions about the relation between the phylogeny of nif genes and the geographical origin of strains carrying these genes.…”
Section: Nodulation Of Lupinus the Fast-growing Isolates Lup21contrasting
confidence: 70%
“…The sequence of the nifH gene showed 99.6% similarity with several strains of Mesorhizobium ciceri reported to nodulate chickpea in Africa (25). These results differ from those obtained previously based on nifD sequences from Bradyrhizobium strains that showed a great degree of local divergence (36); nevertheless, additional studies including other rhizobial species from various geographical locations should be performed to establish definitive conclusions about the relation between the phylogeny of nif genes and the geographical origin of strains carrying these genes.…”
Section: Nodulation Of Lupinus the Fast-growing Isolates Lup21contrasting
confidence: 70%
“…Alexandre et al, (2009) reported that temperature greatly affected the growth and symbiotic performance of Rhizobia. Maatallah et al, (2002) To observe pH tolerance of the rhizobial isolates, they were grown in YEMA medium by adjusting pH to 5-9 and the plates were incubated at 28 0 C for 36 hours. In the present study, optimum pH for rhizobial growth was between 6-7.…”
Section: Effect Of Salt Ph and Temperature On Rhizobium Growthmentioning
confidence: 99%
“…The sequences of the oligonucleotide primers used for amplification of 16S rRNA genes are: Forward primer 41f (5'-GCTCAAGATTGAACGCTGGCG-3'); Reverse primer 1488r (5'-GTTACCTTGTTACGACTTCACC-3') (Maatallah et al, 2002). The stock solution (100 ng ml -1 ) of primers was prepared by reconstituting lyophilized primers in sterilized deionized (milliQ) water and stored at 20°C.…”
Section: Primersmentioning
confidence: 99%